Developing Creative Business Models – The OctoProz Tool - Voigt, Matthias; Ortbach, Kevin; Plattfaut, Ralf; Niehaves, Björn (Eighth International Conference on Design Science Research in Information Systems and Technology (DESRIST), 2013)
Business models are of great importance for business innovation. They can be understood as conceptual models that describe how organizations create and deliver value. Their creation is increasingly supported by information technology artifacts, as information technology facilitates information sharing, allows for continuous modification, and supports complex calculations. In this paper, we introduce a new prototype to create process-oriented business models: the OctoProz tool. We build up on creativity support system literature, present the design of the artifact, and discuss its significance for both research and practice. We close with an outlook on the evaluation of OctoProz.